2022
DOI: 10.1021/acs.jafc.2c07594
|View full text |Cite
|
Sign up to set email alerts
|

Novel Peptide from the Hydrolysate of Hybrid Sturgeon (Acipenseridae) Spinal Cord: Isolation, Identification, and Anti-proliferative Effects in Human Cervix Cancer Cells

Abstract: Anti-proliferative peptides have recently attracted attention for their excellent bioactivity and biocompatibility. In this paper, five novel anti-proliferative peptides were identified from the hydrolysate of hybrid sturgeon spinal cord (HSSC). In addition, the structure−activity relationship of the novel anti-proliferative peptides was explored. In vitro experiments indicated that the peptide "VDSVLDVVRK" presented the highest inhibition of HeLa cell growth in all samples (IC 50 = 2.5 μM). VDSVLDVVRK showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…14 In the past decade, China's sturgeon production has increased dramatically. 15 Raposo et al studies indicated that sturgeon meat as a byproduct of caviar was not effectively utilized. 16 Our previous studies have focused on the exploration of the flavor of steamed sturgeon meat, and these results showed that umami and saltiness were the characteristic flavors of steamed sturgeon meat.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In the past decade, China's sturgeon production has increased dramatically. 15 Raposo et al studies indicated that sturgeon meat as a byproduct of caviar was not effectively utilized. 16 Our previous studies have focused on the exploration of the flavor of steamed sturgeon meat, and these results showed that umami and saltiness were the characteristic flavors of steamed sturgeon meat.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Liu et al showed that seven novel umami peptides (HLQLAIR, DPLRGGYY, LLLPGELAK, AGLQFPVGR, GYSFTTTAER, AGFAGDDAPR, and DAGVIAGLNVLR) were isolated from Takifugu rubripes, which possessed excellent umami characteristics . In the past decade, China’s sturgeon production has increased dramatically . Raposo et al studies indicated that sturgeon meat as a byproduct of caviar was not effectively utilized .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the trypsin hydrolyzed fraction of MW < 1 kDa, produced from the spinal cord of hybrid sturgeon ( Acipenseridae ), showed 34.84 ± 2.86% antiproliferative activity against HeLa cells at a concentration of 200 μg/mL. Additionally, this peptides fraction displayed a proliferative activity of 72.70 ± 2.46% on L929 cells, indicating no significant cytotoxicity ( Han et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%